Abbott & Costello. The complete Universal Pictures collection. [Discs 1-2] [videorecording (DVD)] - Sutherland, A. Edward (Albert Edward), 1897-1973; Lubin, Arthur, 1901-1995; Abbott, Bud, 1897-1974; Costello, Lou; Jones, Allan, 1907-1992; Kelly, Nancy, 1921-1995; Cummings, Robert, 1908-1990; Frawley, William, 1887-1966; Powell, Dick, 1904-1963; Foran, Dick, 1910-1979; Biggers, Earl Derr, 1884-1933; Horman, Arthur T., 1905-1964 (Universal Studios Home Entertainment, 2008)
One night in the tropics: Bud and Lou get mixed up in a "Love insurance" scheme. Buck Privates: Bud and Lou accidentally enlists in the U.S. Army and stumble through basic training. In the navy: Bud and Lou are sailors who must help a famous crooner keep his identity. Hold that ghost: Bud and Lou accidentally inherit a "haunted" house where a gangster stashed his loot.